2022
DOI: 10.1007/s11356-022-24785-w
|View full text |Cite
|
Sign up to set email alerts
|

An exposure to endocrine active persistent pollutants and endometriosis — a review of current epidemiological studies

Abstract: Widespread exposure to persistent pollutants can disrupt the bodies’ natural endocrine functions and contribute to reproductive diseases like endometriosis. In this review, we focus at the relationship between endocrine-disrupting chemicals (EDCs), including metals and trace elements, organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), polybrominated biphenyls (PBBs), poly-brominated diphenyl ethers (PBDEs), polychlorinated dibenzodioxin (PCDDs), polychlorinated dibenzofurans (PCDFs), and per- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…There is growing concern regarding environmental exposures and their relation to public health. It has been suggested that endometriosis and other hormone-sensitive conditions are influenced by environmental exposures, in particular endocrinedisrupting chemicals (EDCs) [11,12,13 && ,…”
Section: Endocrine-disrupting Chemicalsmentioning
confidence: 99%
“…There is growing concern regarding environmental exposures and their relation to public health. It has been suggested that endometriosis and other hormone-sensitive conditions are influenced by environmental exposures, in particular endocrinedisrupting chemicals (EDCs) [11,12,13 && ,…”
Section: Endocrine-disrupting Chemicalsmentioning
confidence: 99%
“…1,[81][82][83] Recent research has shed light on the association between air pollution and endometriosis, revealing the potential adverse effects of airborne contaminants on women's reproductive health. 18,20,84 PM2.5 4,85 and PAHs, 86 two common components of air pollution, have garnered particular attention in relation to endometriosis. PM2.5 refers to tiny particles with a diameter of ≤2.5 microm suspended in the air.…”
Section: A Ir Pol Lu Tion a N D E N Dom Etr Iosismentioning
confidence: 99%
“…Air pollution, a pervasive and persistent environmental issue in urban areas and industrial regions, has been identified as a significant factor in the development and progression of various health conditions 1,81–83 . Recent research has shed light on the association between air pollution and endometriosis, revealing the potential adverse effects of airborne contaminants on women's reproductive health 18,20,84 …”
Section: Air Pollution and Endometriosismentioning
confidence: 99%
“…Those tests are divided into mammalian tests, mostly in rodents, and non-mammalian tests (in fishes, amphibians, and birds) [ 10 ]. Epidemiological studies can also be used when they investigate the relationship between exposure to a substance and changes in endocrine function in human populations [ 11 ]. …”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies can also be used when they investigate the relationship between exposure to a substance and changes in endocrine function in human populations [ 11 ].…”
Section: Introductionmentioning
confidence: 99%